PENINGKTAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MENGGUNAKAN PENDEKATAN KOOPERATIF TIPE TGT - Rahayu, Jenny (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Through this research the writer applied kooperatif mode TGT in processes learning for there are many student. Obsevational stage is describe to plot, implement, and step-up study results. Type of this research is observational action braze, with use qualitative approaching and quantitative one consisting of two cycles. Observational student of class four and observational. Analisis’s result to learning planning on. Cycle is 83,95 experience step-ups on tehe second cycle, by derived 92,9. Result observinging to activity learns in learning on I, cycle is 77,1 experience step-ups on the second is 85,4. Result observinging to student activity in learning on I cycle is 70,85 experience step-ups on the second cycle, by derived 83,3. Learned result before perfom research average 31,25 on the second cycle, average 83,5. In short, the research action class uses kooperatif mode TGT could increase the student’s study result for exact sicience course. Kata kunci : hasil belajar, IPA, model, kooperatif tipe tgt